Q.4 - Nguyễn, Cừ; Nguyễn, Anh Vũ (H., 2010)
Giới thiệu các tác phẩm thơ của nhiều tác giả: Khuyết Danh, Nguyễn Thế Long, Nguyễn Trọng Đông, Trần Lê Hương, Nguyễn Văn Đức, Phan Trọng Bình, Lê Thành Lập...
Keywords: Văn học Việt Nam -- Thế kỷ XX; Thơ ca Việt Nam -- Thế kỷ XX; Thơ cách mạng -- Thế kỷ XX -- Việt Nam